Comparison of skillful vs. less skilled young soccer players on anthropometric, maturation, physical fitness and time of practice - de Gouvea, M. A.; Serpeloni Cyrino, E.; Valente-dos-Santos, J.; Silva Ribeiro, A.; Rodrigues Pereira da Silva, D.; Ohara, D.; Coelho e Silva, M. J.; Vaz Ronque, E. R. (International Journal of Sports Medicine, 2017)
This study compared maturation, body composition and physical fitness between youth soccer athletes with different technical skills levels. Sixty-two young athletes (11-17 years) were categorized dichotomously in more skilled (n=31) and less skilled (n=31) groups based on 3 specific technical tests (Dribbling Speed Test [DST], Shuttle Dribble Test [SDT] and Slalom Dribble Test [SLDT]). Chronological and skeletal age, time of practice, body composition and 4 physical fitness tests were performed for comparisons. As expected, the 3 technical tests were correlated (r=0.47-0.54, P<0.05). More skilled subjects in DST and SDT showed (respectively) higher time of practice (effect size [ES]=0.72 and 0.90), and greater performance sit-ups (ES=1.23 and 0.81), squat jump (ES=1.10 and 1.08), countermovement jump (ES=1.11 and 1.10), and Yo-Yo test (ES=1.17 and 1.40) compared to the less skilled subjects (P<0.05). However, more skilled subjects in SLDT showed greater performance (P<0.05) only in the squat jump (ES=0.67) and Yo-Yo tests (ES=0.83). The results suggest that technical performance is associated with greater time of practice and some physical capabilities. Moreover, the DST and SDT tests seem to be good options to discriminate technical performance in youth soccer athletes.